Процесс индивидуации как ключ к интерпретации главного героя романа Федора Достоевского „Бесы” - Stryjakowska, Anna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to interpret Nikolay Stavrogin, the main character of Fyodor Dostoyevsky’s novel The Possessed, in the key of the analytical psychology. It is argued that Stavrogin may be undergoing the process of individuation by dealing with the collective unconscious. The attention is drawn particularly to the character of Matryosha, who can be perceived as the protagonist’s anima, showing him the way out of the tragic impasse.